Innovation in Event Management: Do Creative Culture and Resilience Matter? - Kurniawan, Buyung; Sari, Komala; Suci, Afred (Universitas Lancang Kuning, 2025)
This current study investigates the relationships between job demands, creative culture, employee resilience, and innovative work behavior within event management firms in Pekanbaru, Indonesia, utilizing a sample of 112 respondents and employing Hayes PROCESS Macro model 4 and model 8. Drawing on the Job Demands-Resources (JD-R) theory, the research found that job demands negatively impacted creative culture. Creative culture fully mediated the relationship between job demands and innovative work behavior, underscoring its vital role as a job resource. However, despite visual trends, employee resilience did not statistically moderate the effect of job demands on either creative culture or innovative work behavior. These findings suggest that in high-pressure event management contexts, organizational resources like creative culture are more potent in fostering innovation than individual resilience in buffering job demands. The study contributes to JD-R theory by extending its application to a dynamic sector and offers practical implications for cultivating creative environments.